In Situ Monitoring of Cu(In1−x,Gax)Se2 Composition and Target Poisoning by Real Time Optical Emission Spectroscopy During Deposition From a Hybrid Sputtering/Evaporation Process - Posada, Jorge; Bousquet, Angélique; Jubault, Marie; Lincot, Daniel; Tomasella, Eric (Plasma processes and polymers, 2016)
Cu(In1−x,Gax)Se2 (CIGS) thin films can be deposited with a high versatility of composition by a hybrid one‐step co‐sputtering/evaporation process. In this paper, plasma analysis is performed with an optical emission spectroscopy non‐contact tool, following light emissions from different plasma species: sputtered copper, gallium, indium but also evaporated selenium. The variations of plasma characteristics are correlated with target self‐bias voltage. Hence, the selenium flow threshold avoiding target poisoning and the main parameter controlling the CIGS composition are determined. This study allows us to set up a process calibration method by means of correlation between the selenium evaporation temperature and the elemental composition of the deposited thin film. Thanks to OES analysis, we correlate the intensity ratio measurements to the final product composition to better control the stoichiometry of Cu(In1−x,Gax)Se2 CIGS thin films, as absorbers in photovoltaic cell. The impact of the target poisoning by evaporated selenium was investigated in a hybrid co‐sputtering/evaporation process. Thereby, we demonstrated that the target poisoning have a direct effect on the final composition of the CIGS‐like absorbers. This effect is greater when the system switches in the Compound Sputtering Mode. Thus, it can be established that the sputtering modes detected using the OES system can be well correlated with the final product deposited.